(3fHPI dWjaI aj GdeRGQGJ GdTQjaIs - (3jSf Hf eUWaj MSH Gddg GdaQVjs
(3ChdgG (B:s
(3hHYO agPg fHPI dWjaI ai GdeRGQGJ GdTQjaI CPcQ ajgG HYV ef Jhai HOeTb hZjQgG ef CQV GdTGe ef GdCfHjGA Ydjge GdUdGg hGdSdGe Ke ef GdUMGHg s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hCNjQkG hHGWfkG hXGgQkG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B314 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ (B((3LOjO (B251) s
Keywords: (3GdJGQjNs